SPA - A system for analysis of indoor team sports using video tracking and wireless sensor network - Wilhelm, P.; Monier, E; Thomas, P.; Ruckert, U. (Proceedings of 6th International Symposium on Image and Signal Processing and Analysis (ISPA), 2009, 2009)
This paper presents a sport analysis system (SPA - Sport Performance Analyzer), consisting of a high resolution video system together with a wireless sensor network for collecting position data and physiological data of sport players during training or competition. The combination of the two data streams provides a new performance analysis and visualization solution for indoor team sports.